Electrocatalytic CO2 Reduction: From Homogeneous Catalysts to Heterogeneous-Based Reticular Chemistry - Abdulhadi A. Al-Omari (Molecules, 2018)
CO2, emitted mainly from fossil fuel combustion, is one of the major greenhouse gases. CO2 could be converted into more valuable chemical feedstocks including CO, HCOOH, HCHO, CH3OH, or CH4. To reduce CO2, catalysts were designed and their unique characteristics were utilized based on types of reaction processes, including catalytic hydrogenation, complex metal hydrides, photocatalysis, biological reduction, and electrochemical reduction. Indeed, the electroreduction method has received much consideration lately due to the simple operation, as well as environmentally friendly procedures that need to be optimized by both of the catalysts and the electrochemical process. In the past few decades, we have witnessed an explosion in development in materials science—especially in regards to the porous crystalline materials based on the strong covalent bond of the organic linkers containing light elements (Covalent organic frameworks, COFs), as well as the hybrid materials that possess organic backbones and inorganic metal-oxo clusters (Metal-organic frameworks, MOFs). Owing to the large surface area and high active site density that belong to these tailorable structures, MOFs and COFs can be applied to many practical applications, such as gas storage and separation, drug release, sensing, and catalysis. Beyond those applications, which have been abundantly studied since the 1990s, CO2 reduction catalyzed by reticular and extended structures of MOFs or COFs has been more recently turned to the next step of state-of-the-art application. In this perspective, we highlight the achievement of homogeneous catalysts used for CO2 electrochemical conversion and contrast it with the advances in new porous catalyst-based reticular chemistry. We then discuss the role of new catalytic systems designed in light of reticular chemistry in the heterogeneous-catalyzed reduction of CO2.